1999
DOI: 10.1002/(sici)1096-8628(19990205)88:1<61::aid-ajmg11>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Population studies of polymorphisms of the serotonin transporter protein gene

Abstract: The range of allele frequency variation in humans for any locus that may have functionally important genetic variation needs to be documented. Therefore, we tested two polymorphisms at the serotonin transporter protein locus (SLC6A4) in samples from seven specific populations from five continental regions. We studied the promoter polymorphism which is reported to have functional significance and to be associated with anxiety- and depression-related phenotypes [Lesch et al., 1996: Science 274:1527-1531], and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(45 citation statements)
references
References 28 publications
6
39
0
Order By: Relevance
“…3, which shows that the 5-HTTLPR short allele (14 repeats) had a somewhat lower frequency (0.42) in healthy Caucasian population than the 5-HTTLPR long allele (16 repeats, frequency = 0.58). These results are in a good correlation with the Caucasian population data of Gelertner et al [23]. According to our knowledge, no other size variations have been found among Caucasians, however, other repeat numbers than 14 and 16 were shown in Japanese (19,20 and 22 repeats) [24] and Israeli populations (18 repeats) [25].…”
Section: Resultssupporting
confidence: 42%
“…3, which shows that the 5-HTTLPR short allele (14 repeats) had a somewhat lower frequency (0.42) in healthy Caucasian population than the 5-HTTLPR long allele (16 repeats, frequency = 0.58). These results are in a good correlation with the Caucasian population data of Gelertner et al [23]. According to our knowledge, no other size variations have been found among Caucasians, however, other repeat numbers than 14 and 16 were shown in Japanese (19,20 and 22 repeats) [24] and Israeli populations (18 repeats) [25].…”
Section: Resultssupporting
confidence: 42%
“…In other words, the S form of this variant is associated with lower basal and induced transcriptional efficiency of the SERT gene promoter, resulting in lower serotonin reuptake activity and longer serotonergic activity than for the L form [4,5]. Both the 5-HTTLPR and the VNTR genetic polymorphisms have been extensively investigated in genetic association studies for various complex behavioral traits and disorders [5,[9][10][11][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 94%
“…Ethnic genotype 2.2 ± 0.9 2.0 ± 0.6 1.0 ± 0.8 * * P < 0.05, L/L vs. S/S and S/L group. differences in the 5-HTTLPR and VNTRs in intron 2 of healthy subjects in different nations are reported in Tables 4 and 5 [12][13][14][15][23][24][25][26][27][28]. The allele frequencies and genotype frequencies of Chinese people demonstrated in this study were similar to those of Korean and Japanese but different from those reported in Western countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphism of the serotonin transporter 5HTT was investigated using specific primers for 5HTTLPR suggested by Gelernter et al (1999). PCR amplification was performed in accordance to Nonnis Marzano et al (2008).…”
Section: Methodsmentioning
confidence: 99%